ANALISIS PERBANDINGAN PENERAPAN PENGUKURAN KINERJA BERBASIS BALANCE SCORECARD PADA BADAN USAHA BERBENTUK KOPERASI KONVENSIONAL DAN KOPERASI SYARIAH ( STUDI KASUS PADA PRIMKOPKAR PT.WONOSARI JAYA DAN KOPERASI SYARIAH ANNISSA ) - AMALIA RAHAYU, RETNO Amalia (Jurnal Akuntansi AKUNESA, 2013)
The differences charateristic on each cooperative can be affect performance of thecooperative. Therefore, are required performance measurement with balance Sorecardsytem to asses all of the cooperative performance. This type of study is qualitativeresearch using discriptive approach. Data analysis used Balance Scorecard methodeby measuring cooperative performance with four perspektif. The methode of dataanalysis used is descriptive analysis. Based on the result of analysis, performace ofPrimer Koprasi Karyawan PT.Wonosari after using Balanced Scorecard has morebetter than Islamic Cooperative “An-nissa”. But both of the cooperation performancecan be able reflection the vision, mission and strategy that has been set.Keywords : Cooperative, Performance, Balance Scorcard.